2002
DOI: 10.1177/104973102237470
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mobile Crisis Services on the Use of Community-Based Mental Health Services

Abstract: Objective: To examine the impact of community-based mobile crisis services on postcrisis community-based mental health service use and user characteristics related to likelihood of postcrisis service use. Method: Differences in use of postcrisis mental health services and timing between a community-based intervention cohort and a matched hospital-based cohort were assessed using a Cox proportional hazards model. Results: A mobile crisis intervention consumer was 17% more likely to receive community-based menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…7,8 Even without police officers, mobile crisis services can enhance the subsequent use of mental health services in people who are disadvantaged or disenfranchised, in particular people with serious and persistent mental illness and the homeless. [9][10][11][12][13] The only controlled evaluation of a service involving police and mental health clinicians was a small retrospective US study, not a controlled before-and-after design. This showed that the crisis team led to fewer subsequent admissions, as well as greater police and consumer satisfaction over 3 months.…”
mentioning
confidence: 99%
“…7,8 Even without police officers, mobile crisis services can enhance the subsequent use of mental health services in people who are disadvantaged or disenfranchised, in particular people with serious and persistent mental illness and the homeless. [9][10][11][12][13] The only controlled evaluation of a service involving police and mental health clinicians was a small retrospective US study, not a controlled before-and-after design. This showed that the crisis team led to fewer subsequent admissions, as well as greater police and consumer satisfaction over 3 months.…”
mentioning
confidence: 99%
“…Scott (2000) and Cowell, Broner, and Dupont (2004) found cost savings in criminal justice expenditures; however, this was also accompanied by an increase in treatment costs (Cowell et al, 2004). In addition, Dyches et al (2002) found MCUs to be more effective than hospital-based mobile crisis services in connecting services and PMI.…”
Section: Mcusmentioning
confidence: 88%
“…The existing research seems to agree that MCUs serve a different population than hospital emergency rooms. The MCU PMI are more likely to have past arrests and/or histories of violence, possess more major disorders, and be homeless (Dyches et al, 2002;Gilling, Dumaine, Stammer, Hillard, & Grubb, 1990;Lamb et al, 1999). These PMI often refuse emergency room treatment or are unaware of a need for treatment and possess fewer capabilities to meet their own physical needs.…”
Section: Mcusmentioning
confidence: 95%
See 2 more Smart Citations